1990
DOI: 10.3164/jcbn.9.205
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional survey on the serum status of lipid, protein, and calcium levels in Nepalese.

Abstract: SummaryThis study examined the physical status (72 males and 69 females) and serum distribution of lipids, protein, and Ca (60 males and 57 females) of people aged 1 to 72 years living in southeastern Nepal. The mean values of height and weight increased with age to adolescence and were the same for both sexes in childhood. Males were taller than females above the 15-19-year age group. There were large weight differences among individuals, with adult males tending to be heavier than adult females. The average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

1994
1994
2005
2005

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 27 publications
2
2
0
Order By: Relevance
“…The mean value of TG over 150 mg/dl was found in the subjects of 20-49 age groups of males and over 50 years old females in area A, and generally the mean values of TG of the subjects tended to be at the higher ranges of the normal. Similar findings have been observed in elsewhere in Nepal [8]. Lim and Heo reported the TG level of 126.0Ϯ0.9 mg/dl in Korean males aged 23 to 72 years [15].…”
Section: Serum Nutritional Components and Relationship Among Themsupporting
confidence: 74%
See 1 more Smart Citation
“…The mean value of TG over 150 mg/dl was found in the subjects of 20-49 age groups of males and over 50 years old females in area A, and generally the mean values of TG of the subjects tended to be at the higher ranges of the normal. Similar findings have been observed in elsewhere in Nepal [8]. Lim and Heo reported the TG level of 126.0Ϯ0.9 mg/dl in Korean males aged 23 to 72 years [15].…”
Section: Serum Nutritional Components and Relationship Among Themsupporting
confidence: 74%
“…The mean values of TP and Alb of the subjects in each age group in both areas were within the ranges considered normal for Japanese (TP, 6.5-7.9 g/dl, Alb, 4.0-5.0 g/dl for combined sexes) [ 13 ]. The TP level of the subjects in this study was about the same as that for the residents in Itahari district, Terai region [8], but to be lower than that of people in an agricultural Chitwan district, Terai region, Nepal [14]. The BUN and UA levels were within the ranges normal for Japanese (BUN, 8-20 mg/dl, for both sexes; UA, 4.0-7.5 mg/dl for males, 3.0-6.5 for females) [13].…”
Section: Serum Nutritional Components and Relationship Among Themmentioning
confidence: 64%
“…Compared with the normal range of TC (150-230 mg/dl), the mean TC level was at the lower range of normal levels (13), whereas the mean value of TG was at the higher range of normal levels in this study. Similar findings of high TG levels have been reported previously for other people (132-165 mg/dl in a remote hilly village, 175 mg/dl for the males in the Itahari district, 98-134 mg/dl for both sexes in the Chitwan district) in Nepal (4,17,18) and 23 to 72-yearold males (126.0±0.9 mg/dl) in Korea (19). The large intake of cereals containing much carbohydrate may have contributed to the higher serum TG level because excess carbohydrate intake is converted to fat in the human body.…”
Section: Discussionsupporting
confidence: 88%
“…The Alb concentration indicates the nutritional status, therefore, young females need more nutrition for pregnancy and breastfeeding infants, suggesting a need to improve nutritional status. The high amounts of Glb, especially γ-Glb, caused higher amounts of total protein (TP) than what is considered normal for the Japanese (6.8-8.2 g/dl for both sexes) (9) and for Itahari residents, an industrial district in the Terai region reported previously (4,10). γ-Glb is a major component of globulin and is known to increase with liver disease, and chronic or acute infectious diseases.…”
Section: Discussionmentioning
confidence: 99%